2016
DOI: 10.14716/ijtech.v7i2.2979
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pyrolyzed Oil from Crude Glycerol using a Microwave Heating Technique

Abstract: Crude glycerol, a by-product of biodiesel production created via transesterification was pyrolyzed using a microwave heating technique in an oxygen-deficient environment. Coconut shell-based activated carbon was used as a catalyst to assist in the heat transfer and the cracking of glycerol into gaseous and liquid products. Investigation into the product yield was conducted by varying the pyrolysis temperature between 300°C and 800°C. The result revealed that liquid and gaseous pyrolysis products yield fell in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Due to the high hydrocarbon content of plastics, the microwave-assisted pyrolysis of plastics would result in high bio-oil yields. difference was more significant when the heating temperature was raised to 400°C and the gaseous product was reduced by 19%, while the liquid product increased by 22% (137). The same authors reported that the highest liquid (bio-oil) product yield was obtained at the heating temperature of 400°C.…”
Section: Organicsmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to the high hydrocarbon content of plastics, the microwave-assisted pyrolysis of plastics would result in high bio-oil yields. difference was more significant when the heating temperature was raised to 400°C and the gaseous product was reduced by 19%, while the liquid product increased by 22% (137). The same authors reported that the highest liquid (bio-oil) product yield was obtained at the heating temperature of 400°C.…”
Section: Organicsmentioning
confidence: 93%
“…In a recent study, it was reported that generally the presence of the catalyst during the microwave-assisted pyrolysis of crude glycerol resulted in an increase in liquid product and a decrease in gaseous product at both the temperatures of 300°C and 400°C (137). At 300°C…”
Section: Microwave-assisted Pyrolysis Of Crude Glycerol As Sole Biomassmentioning
confidence: 99%
“…The heating process acts as the driving force to extract the triglyceride compound from the biological matrix in a shorter period of time (Patil et al, 2011). The method was used by Leong et al (2016), who used microwave heating to obtain pyrolyzed oil from crude glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Leong et al (2016) reported the pyrolysis of crude glycerol using a microwave heating technique to produce pyrolyzed liquid, which can be used as fuels in combustion systems. Glycerol could also be converted to glycerol carbonate (Okoye and Hameed, 2016).…”
Section: Introductionmentioning
confidence: 99%